EFFECT OF DIFFERENT NPK LEVELS AND CHLOROPHYLL CONTENT ON GROWTH AND DEVELOPMENT OF GRAPEFRUIT (CITRUS×PARADISI). (International Journal of Food and Nutritional Sciences, 2023)
The present investigation entitled Effect of different levels of Nitrogen (N) Phosphorus (P2O5) and Potassium (K2O) on growth and development of Grapefruit (Citrus×paradisi) plants were carried out at Agricultural Research Farm, Rama University, Mandhana, Kanpur. The results revealed that the treatment T2 (850 g / plant Nitrogen, 600 g / plant Phosphorus and850 g / plant Potash)was found to be the best in terms of maximum plant height (83.57cm), maximum number of leaves (421.04), maximum number of branches (26.36), maximum stem diameter (3.04 cm), maximum spread of canopy(42.36 cm)and maximum length of inter-nodes (9.68cm)& maximum in chlorophyll content (4.58 mg/g) followed by treatment T9 (800 g / plant Nitrogen, 400 g / plant Phosphorus and500 g / plant Potash) and the minimum was recorded in T4(700g / plant Nitrogen, 400g / plant Phosphorus and 400g / plant Potash).